2020
DOI: 10.3389/fpsyg.2020.589543
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Restrictions and Quarantine COVID-19: Effects on Cardiovascular and Yo-Yo Test Performance in Professional Soccer Players

Abstract: The present study aimed to verify the quarantine’s effects during a serious viral outbreak on the cardiovascular and performance associated with the Yo-Yo test in a sample of professional soccer players. 20 high-level soccer players (n = 20; age: 26 ± 4 years-old; weight: 76.85 ± 6.7 kg; height: 179 ± 6 cm) participated in this study. The intermittent Yo-Yo test was performed pre- and post- COVID-19 quarantine in a random order. During each test, the soccer players’ running performance outcomes were monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 57 publications
2
29
1
10
Order By: Relevance
“…This discrepancy in physical intensity during match between the Japanese national handball team and the previous data [20,23,24] evaluated before the COVID-19 pandemic may be attributed to the prolonged activity restrictions experienced by the Japanese players before rebooting the training camp. Similar adverse effects of the COVID-19-related activity restriction on athletes' cardiovascular performance have been reported in many sports [25][26][27]. Most of our athlete cohort resumed their regular handball training step-by-step after the end of state of emergency in Japan.…”
Section: Heart Rate and Physical Intensity Evaluation Using The Wearable Sensorsupporting
confidence: 71%
“…This discrepancy in physical intensity during match between the Japanese national handball team and the previous data [20,23,24] evaluated before the COVID-19 pandemic may be attributed to the prolonged activity restrictions experienced by the Japanese players before rebooting the training camp. Similar adverse effects of the COVID-19-related activity restriction on athletes' cardiovascular performance have been reported in many sports [25][26][27]. Most of our athlete cohort resumed their regular handball training step-by-step after the end of state of emergency in Japan.…”
Section: Heart Rate and Physical Intensity Evaluation Using The Wearable Sensorsupporting
confidence: 71%
“…They concluded that even though the athletes were training at home three times a week at 65–75% of maximal heart rate, the 40 days of quarantine had an impact on maximal speed, high-intensity running distance, acceleration, and deceleration. However, their maximal aerobic capacity calculated from the Yo-Yo test did not change [ 37 ]. To further assess swimming performance, we used time-ranking points to compare the swimming results of the national championships.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, following the German lockdown for containment of the COVID-19 pandemic, highly trained kayakers and canoeists spent less overall time training each week (−28%) with, on average, shorter training sessions (−15%) and less light-to-moderate physical activity outside of training [ 19 ]. Additionally, de Albuquerque Freire et al [ 20 ] demonstrated that COVID-19-related restrictions and quarantine had adverse effects on professional soccer players’ Yo-Yo Intermittent Recovery Test performance. Therefore, in the context of COVID-19, public health measures such as isolation, curfews, and lockdowns could have resulted in partial or total reversal of the training adaptations (i.e., ‘detraining’) [ 11 , 21 ].…”
Section: Introductionmentioning
confidence: 99%